DEVELOPMENT OF TEACHING MATERIALS EDSK (ENERGI DALAM SISTEM KEHIDUPAN) BASED ON 7 COMPONENTS OF EFFECTIVE LEARNING - Faninda Novika Pertiwi; Nurzatulshima Kamarudin (INSECTA: Integrative Science Education and Teaching Activity Journal, 2023)
The Department of Tadris IPA IAIN Ponorogo in the 2020/2021 school year redesigned the curriculum to become the KKNI. The KKNI is applied to students starting in semester 1 of the 2020/2021 academic year. Where the types of courses and learning carried out are of course different from the previous curriculum. Implementation of learning with KKNI is certainly not as easy as expected. One of the obstacles to implementing the KKNI is the unavailability of the KKNI based lecturer and student handbooks that can be used during the learning process. Based on interviews with several science lecturers who were teaching in semester 1, the teaching materials used were still the teaching materials used in the previous curriculum. For example, when teaching the Energy in Living Systems course, the handbook used is the basic physics textbook used to teach students in the previous semester. This is what causes the buildup of material and is not optimal in linking physics material with other fields and teaching it more contextually. This is what underlies researchers to develop a textbook on energy in living systems based on the seven components of effective learning.